PEMANFAATAN BATU PADAS JENIS LADGESTONE TERAKTIVASI NaOH DAN TERSALUT Fe2O3 SEBAGAI ADSORBEN LARUTAN BENZENA - I Nengah Simpen; I Made Sutha Negara; Ida Ayu Agung Pradnyani (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2011)
This paper describes the adsorption of benzene by ledgestone which was activated with 4 M NaOH and coated with Fe2O3. The proportions of ledgestone and the coating used were of 10 : 1, 50 : 1, and 100 : 1. The aim of this study was to find out the ability of the stone in decreasing benzene concentration in solution. The study included the determination of surface acidity by acid-base titration, characterization of the ledgestone specific surface area by the method of blue methylene, determination of equilibration time of the stone in adsorbing benzene and determination of adsorption capacity of the stone referred to Freundlich isotherm adsorption by the application of gas chromatography.The result showed that the highest surface acidity of 0.2980 mmol/g was given by the ledgestone that was activated with 4 M NaOH and coated with Fe2O3 with the proportion of 10 : 1 and washed by aquadest. This ledgestone also showed the highest adsorption capacity which was 44.1286 ?g/g. The control ledgestone had specific surface area of 35.880 m2/g. The ledgestone that was activated with 4 M NaOH and coated with Fe2O3 resulted in higher adsorption capacity to benzene than the control ledgestone did.